ANALISIS PEMANFAATAN MEDIA MATH PLAYGROUND DALAM PEMBELAJARAN MATEMATIKA KELAS 1 MATERI PENGURANGAN - Ainaya Hanum Lutfia; Widya Kusumaningsih; Sri Suneki (STKIP Subang, 2023)
The progress of science and technology has an impact on various things in human life, one of which has an impact on the world of education. Education in the 21st century has taken advantage of existing technological advances by utilizing interactive learning media and in accordance with student characteristics. Today's students are students who are technologically literate and very familiar with the digital world. Therefore learning media must be interesting, fun and in accordance with the characteristics of students to increase student interest in learning. One of them is by utilizing educational game media in learning. Math Playground is one of the online math games that contains self-evaluation and feedback which can be accessed on the website mathplayground.com which is a free educational game site. This study aims to determine the benefits of Math Playground as a game-based learning medium for learning mathematics in elementary schools. This study used descriptive qualitative method. The subjects of this study were grade 1 students at SD Negeri Petompon 02 Semarang. Sources of data obtained from interviews and observations. The results of this study show that Math Playground has the potential to have a positive impact as an educational game-based learning medium in learning mathematics in elementary schools.